Enterovesical Fistula Caused by a Toothpick. (8th March 2015) - Tombolini, Flavia; Lacetera, Vito; Muzzonigro, Giovanni
Abstract : We present a case of enterovesical fistula caused by an accidental ingestion of a foreign body. A 23-year-old man presented to our hospital with pneumaturia, fecaluria, and abdominal pain but no recent possible causes of enterovesical fistula at anamnesis. Cystoscopy, cystography, and also colonoscopy were not able to detect the fistulous tract. Computer tomography (CT) revealed a fistula between bladder and bowels caused by a toothpick accidentally swallowed 2 years earlier. We tried to remove the foreign body endoscopically by cystoscopy and colonoscopy but with no success. The failure of endoscopic procedures required a surgical treatment. The patient underwent laparoscopic segmental resection of the sigmoid colon to remove the fistulous tract and the foreign body. The cystography revealed no external leakage of contrast from the bladder with complete resolution of the problem.